Labor Regulation and Enterprise Employment in China - Park, Albert; Giles, John; Du, Yang (World Bank, Washington, DC, 2017)
Using data from a national survey of Chinese manufacturing firms conducted in 2009, the authors analyze the impact of implementation of China's 2008 labor contract law on the employment of production workers. The authors found that cities with lax prior enforcement of labor regulations experienced a greater increase in enforcement after 2008 and slower employment growth, and that this finding is robust to inclusion of a rich set of city-level controls and the use of alternative measures of enforcement effort. Although firms affected by the global economic crisis did not report less strict enforcement of the new law, there is evidence that their employment adjustment was less sensitive to enforcement of labor regulations than firms not affected by the crisis.